Alumina ceramic substrate and preparation method thereof
By adopting a flat plate pressing process in the preparation process of alumina ceramic substrate, the problems of bubbles and layering in traditional isostatic pressing are solved, an efficient and simplified production process is achieved, and the mechanical properties of the substrate are improved.
Patent Information
- Application Number
- CN202411779562.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-08
AI Technical Summary
Existing alumina ceramic substrates are prone to bubbles or stratification during isostatic pressing, and the process is complicated and the production efficiency is low.
The flat plate pressing process is used instead of the traditional isostatic molding process. By bonding the rough surfaces of the alumina cast film to each other, and applying a wetting modifier to the smooth surface, it forms a ceramic green body with high connection strength and exhaust thorough exhaust.
It effectively reduces bubbles and layering phenomena, simplifies the production process, reduces production costs, improves production efficiency, and improves the mechanical strength of the ceramic substrate.
Smart Images

Figure CN119774987A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic substrates, and more specifically, to an alumina ceramic substrate and a preparation method thereof. Background Art
[0002] Ceramic substrates are mainly made of alumina. Due to their excellent electrical insulation properties, high thermal conductivity and excellent soft solderability, they play an important role in high-power power semiconductor modules. At present, the main preparation method for ceramic substrates is the tape casting process. However, for ceramic green bodies with a thickness greater than 2.0 mm, the thickness of the tape casting machine is often not up to the requirements. Therefore, in general, the tape casting substrate green bodies need to be stacked to the required thickness, and then pressed to form substrate green bodies.
[0003] The traditional method of laminating cast films generally adopts isostatic pressing, which is as follows: first stack two or more cast films together, cover them with silicone pads, put them into a PE bag and evacuate them, and then press them through a warm isostatic press or a cold isostatic press to bond the multi-layer films together to form a substrate green body; however, after the substrate green body is subjected to warm or cold isostatic pressing, small bulges, bubbles or stratification often appear on the surface, which greatly reduces the yield of the substrate. In addition, the process is complicated and the production efficiency is low.
[0004] In order to solve the problem of small bulges, bubbles or delamination in the substrate green body processed by the lamination process of isostatic pressing, the lamination process in the prior art often improves the adhesion between the film layers during the pressing process. For example, the preparation method of the aluminum nitride ceramic substrate in patent CN106116589A includes the following steps: (1) preparing casting slurry; (2) casting molding; (3) stamping; (4) solvent coating: coating both sides of the monolithic green body with organic solvent; (5) lamination: stacking the monolithic green bodies coated with organic solvent in step (4) and vacuum packaging; (6) isostatic pressing; (7) debinding; (8) sintering to obtain the aluminum nitride ceramic substrate. By coating the solvent on the contact surface of the laminated green body, the green body is uniform and the sintered product has good density. However, this process relies on isostatic pressing, which requires vacuuming in a PE bag, and the process is cumbersome. In the actual isostatic pressing process, vacuuming cannot completely avoid the residual gas in the PE bag, and it is also inevitable that the surface of the PE bag will be deformed and wrinkled during vacuuming, making it very easy for bubbles and bulging to appear on the surface of the blank in the PE bag when heated. When other pressing processes are used, it is impossible to take into account both the connection strength between the film layers and the debonding effect. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects and shortcomings of the existing alumina ceramic substrates and provide a method for preparing an alumina ceramic substrate to replace the traditional isostatic pressing process, solve the undesirable phenomena of bubbles or stratification, and simplify the production process, reduce production costs and improve production efficiency.
[0006] Another object of the present invention is to provide an alumina ceramic substrate obtained by the above preparation method.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] The present invention provides a method for preparing an alumina ceramic substrate, comprising the following steps:
[0009] S1, obtaining an alumina cast film, and marking two sides of the cast film as a smooth surface and a rough surface respectively according to the surface roughness;
[0010] S2, laminating the cast films to each other through the rough surfaces to form a primary film sheet;
[0011] S3, coating the smooth surface of the primary membrane with a wettability modifier, and then bonding the primary membranes to each other through the treated smooth surfaces to form a substrate green body;
[0012] S4, after pasting release films on both sides of the substrate green body, pressing the plates together, removing binder, and sintering to obtain an alumina ceramic substrate.
[0013] The preparation method of the alumina ceramic substrate of the present invention can adopt a flat pressing process to replace the traditional isostatic pressing process. In addition to solving the undesirable phenomenon of bubbles or stratification, it can also simplify the production process. In the lamination process, the rough surfaces of two cast films are directly attached to each other and then pressed. The two rough surfaces cannot be tightly attached to each other, and the gas can be discharged through the gap between the contact surfaces, effectively reducing the bulging and bubble problems caused by incomplete exhaust. The smooth surface of the outer side of the primary diaphragm formed by bonding is coated with a wettability modifier and then bonded to each other, which can reduce bubbles at the bonding interface and improve the bonding strength after pressing. Moreover, due to the high density of the smooth surface, the coated wettability modifier is not easy to penetrate into the interior of the diaphragm, and the modifier is also easy to be completely ablated during the debinding process. The ceramic green body with high connection strength between the film layers and complete exhaust can be formed by flat pressing.
[0014] The alumina cast film of the present invention is prepared by tape casting of ceramic slurry; preferably, the solid content of the ceramic slurry is 67-70wt%. Slurry with a higher solid content can provide a larger area of contact between particles, and the close contact between particles reduces the stress concentration caused by drying or sintering, making the green body more stable during the drying and sintering process, reducing the risk of deformation and cracking.
[0015] The present invention has no special limitation on the ceramic slurry, and the purpose of the present invention can be achieved by using conventional alumina ceramic slurry in the art; illustratively, the components of the ceramic slurry include, by weight: 90-98 parts of alumina powder, 2-10 parts of ZrO and / or ZnO powder, 20-35 parts of solvent, and 5-25 parts of additives; and pass through a 2-3 μm sieve.
[0016] Optionally, the auxiliary agents include but are not limited to cosolvents, dispersants, binders and plasticizers; preferably, by weight, the auxiliary agents include: 3-5 parts of flux, 0.5-2 parts of dispersant, 5-10 parts of binder, and 2-5 parts of plasticizer.
[0017] Specifically, the solvent is selected from any one of ethanol, toluene or butanone.
[0018] The flux is selected from one or more of SiO2, CaO, MgO and Y2O3.
[0019] The dispersant is selected from castor oil or phosphoric acid ester.
[0020] The binder is selected from polyvinyl butyral.
[0021] The plasticizer is selected from dioctyl phthalate.
[0022] In some embodiments, in step S1, the roughness of the smooth surface is ≤0.2 μm, and the roughness of the rough surface is 0.3-0.5 μm.
[0023] In some embodiments, in step S3, the wettability modifier includes the following components in parts by weight:
[0024] 100 parts of organic-inorganic hybrid nano powder, 3-8 parts of dispersant, 8-12 parts of water, and 60-80 parts of C1-C4 fatty alcohol.
[0025] Optionally, the wettability modifier has a viscosity of 100-150 cp at 25°C.
[0026] Optionally, the dispersant is selected from sodium carboxymethylcellulose.
[0027] The organic-inorganic hybrid nano powder is synthesized by a sol-gel method using inorganic and organic substances.
[0028] Optionally, in the organic-inorganic hybrid nanopowder, the organic matter is selected from dimethyldichlorosilane ((CH3)2SiCl2) and / or diphenyldichlorosilane ((C6H5)2SiCl2), and the inorganic matter is selected from at least one of magnesium oxide, titanium dioxide, calcium oxide, silicon oxide, vanadium oxide or lanthanum oxide; after the two primary diaphragms are pressed together, the organic-inorganic hybrid nanopowder coated between the diaphragms forms uniform pores, which helps to remove the organic matter in the entire green sheet after uniform decomposition in the subsequent kiln debinding process, thereby promoting the debinding process.
[0029] Preferably, organic silicon-magnesium oxide hybrid nanopowder is used. Magnesium oxide remains in the membrane and can be used as a sintering aid to effectively reduce the sintering temperature of alumina ceramics. At the same time, it can play the role of a microstructure stabilizer, reduce the difference in grain boundary energy by refining the grains, and inhibit discontinuous grain growth. The refinement effect helps to improve the mechanical strength of the ceramic substrate.
[0030] Optionally, the organic-inorganic hybrid nanopowder is synthesized by a sol-gel method, and then dried and sintered to obtain the powder.
[0031] The D50 particle size of the organic-inorganic hybrid nano powder is 50-200 nm; preferably, the D50 particle size of the organic-inorganic hybrid nano powder is 80-120 nm.
[0032] Optionally, the C1-C4 fatty alcohol includes but is not limited to at least one of ethanol, n-propanol and isopropanol.
[0033] In some embodiments, in step S4, the release film is a silicone oil release film with a film thickness of 150-250 μm and a roughness of 0.01-0.1 μm. Preferably, the peeling force is 5-8 g.
[0034] In some embodiments, in step S4, the flat plate pressing parameters are: pressing temperature 50-70°C, pressure 10-15Mpa, and holding time 10-30s. The preferred pressing parameters of the present invention are conducive to heating-softening-pressing the green sheet, so that the internal organic molecular chains undergo glass transition, and are bonded together through the hinge of chemical bonds to improve the bonding strength.
[0035] In some embodiments, the flat plate pressing step is: after laminating release films on both sides of the substrate green body, laminating green body gaskets on both side surfaces, and then placing on a pressing plate of a flat plate pressing device for pressing.
[0036] Preferably, the green gasket includes an upper green gasket and a lower green gasket, the thickness of the upper green gasket is 2-4 times the thickness of the primary diaphragm, the thickness of the lower green gasket is 0.5-1 times the thickness of the primary diaphragm, and the green gasket can fix the stacked products to prevent dislocation.
[0037] During the flat plate pressing process, the applied pressure will be transmitted from top to bottom to the substrate green product through the upper green gasket. The thicker upper green gasket can effectively disperse and withstand the pressure, and overflow to the surroundings to wrap the green product to a certain extent, which is conducive to reducing the displacement of the green product; and the thinner lower green gasket can better adapt to the shape of the mold and the contour of the green product, making it easier for the green product to maintain its original shape and size during the pressing process, which is very helpful to improve the molding accuracy of the product.
[0038] Preferably, the material of the green spacer is the same as that of the substrate green product.
[0039] Optionally, the mold design of the flat plate vulcanizer is as follows: the flat pressing plates at the upper and lower ends are provided with a first boss and a second boss respectively, the first boss has an arc-shaped cross section, its width gradually increases from top to bottom, and the bottom area completely covers the base plate green body; the second boss has a trapezoidal cross section, and the bottom surface of the first boss is flush with the upper surface of the second boss. The first boss with an arc-shaped structure is conducive to dispersing pressure during the pressing process and improving the uniformity of the forces in all directions; and the trapezoidal structure of the second boss can improve stability.
[0040] In some embodiments, in step S4, the specific step of debinding is: debinding the substrate green body at 120-350° C., with a heating rate of 0.5-0.15° C. / min.
[0041] In some embodiments, in step S4, the sintering conditions are: sintering temperature 1535-1545° C., and holding time 2-3 hours.
[0042] Optionally, the sintering process parameters are:
[0043] Heating stage: 360~850℃, heating rate: 1~2℃ / min;
[0044] The heating stage is 850~1535℃, and the heating rate is 1.5~2.5℃ / min.
[0045] Keep warm at 1535-1545℃ for 2-3h;
[0046] The temperature drop period is 1535~1000℃, and the temperature drop rate is 1~2℃ / min;
[0047] The temperature drop period is 1000~700℃, and the temperature drop rate is 0.1~1℃ / min;
[0048] Cooling stage: 700~25℃, natural cooling.
[0049] The invention protects an alumina ceramic substrate, which is made by the preparation method of the alumina ceramic substrate.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] The invention provides a method for preparing an alumina ceramic substrate. The method can adopt a flat plate pressing process to replace a traditional isostatic pressing process. In addition to solving the problem of bubbles or stratification, the manufacturing process can be simplified. In the lamination process, the rough surfaces of two cast films are directly attached to each other and then pressed. The two rough surfaces cannot be tightly attached to each other, and the gas can be discharged through the gap between the contact surfaces, effectively reducing the problems of bulging and bubbles caused by incomplete exhaust. The smooth surfaces on the outer sides of the primary diaphragms formed by the lamination are coated with a wettability modifier and then attached to each other, which can reduce bubbles on the lamination interface and improve the bonding strength after pressing. Moreover, since the density of the smooth surface is relatively high, the coated wettability modifier is not easy to penetrate into the interior of the diaphragm, and the adhesive is easy to be discharged. The ceramic green body with high connection strength between the film layers and complete exhaust can be formed by flat plate pressing. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a structural schematic diagram of a flat plate pressing process of a method for preparing an alumina ceramic substrate in Example 1 of the present invention.
[0053] Figure 2 The present invention Figure 2 A partial enlarged view of .
[0054] Figure 3 This is a morphology diagram of an alumina ceramic substrate according to Example 1 of the present invention.
[0055] Figure 4 This is a morphology diagram of an alumina ceramic substrate of Comparative Example 4 of the present invention.
[0056] Among them, 1. flat pressing plate; 11. first boss; 12. second boss; 21. upper green sheet gasket; 22. lower green sheet gasket; 3. substrate green sheet; 4. release film; 5. wettability modifier layer. DETAILED DESCRIPTION
[0057] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0058] Example 1
[0059] A method for preparing an alumina ceramic substrate comprises the following steps:
[0060] S1, tape casting to prepare cast film, punching and tableting;
[0061] Specifically, a cast film with a thickness of 1.19 mm was prepared by using ceramic slurry tape casting, and the cast film was punched into 140*140 mm specifications using a punching machine, and the obtained cast film was marked on the A side (smooth side) and the B side (rough side);
[0062] The solid content of the ceramic slurry is 68wt%. The components of the ceramic slurry include, by weight: 94 parts of alumina powder, 6 parts of ZnO powder, 27 parts of solvent, 4 parts of flux, 1.5 parts of dispersant, 8 parts of binder, and 3 parts of plasticizer.
[0063] Among them, the solvent is selected from ethanol and toluene in a mass ratio of 1:1; the flux is selected from MgO and Y2O3 in a mass ratio of 2:1; the dispersant is selected from phosphate ester (Jiangsu Hai'an Petrochemical Company, No. 600); the binder is selected from polyvinyl butyral (B60H, Kuraray International Trade (Shanghai) Co., Ltd.); the plasticizer is selected from dioctyl phthalate (Zhejiang Qing'an Chemical Co., Ltd.); the ceramic slurry is passed through a 2μm sieve.
[0064] Measured by TR200 roughness tester, the roughness of surface A is 0.1-0.2μm, and the roughness of surface B is 0.3-0.5μm.
[0065] S2, laminating the cast film sheets to each other via the B surface to form a primary film sheet;
[0066] S3, coating the A surface of the primary membrane with a wettability modifier, and then bonding the primary membranes to each other via the treated A surfaces to form a substrate green body; the primary membrane is used as a laminated unit, and the substrate green body in this embodiment consists of two laminated units.
[0067] The wettability modifier is a mixture of the following components in parts by mass: 100 parts of organosilicon-magnesium oxide hybrid nanopowder, 5 parts of sodium carboxymethyl cellulose, 10 parts of water, and 70 parts of ethanol. The viscosity of the wettability modifier at 25° C. is 100 cp.
[0068] The median diameter D50 of the organosilicon-magnesium oxide hybrid nanopowder used in this embodiment is 80 nm. The organosilicon-magnesium oxide hybrid nanopowder of this embodiment is synthesized by a sol-gel method from a magnesium source and a small molecule organosilicon compound; the small molecule organosilicon compound is dimethyldichlorosilane ((CH3)2SiCl2).
[0069] The sol-gel method for preparing the organosilicon-magnesium oxide hybrid nanopowder specifically comprises the following steps:
[0070] (1) A certain amount of MgCl2·6H2O is prepared into a magnesium chloride aqueous solution with a concentration of 3 mol / L, 30% ammonia water is diluted 20 times as a precipitant, and dimethyldichlorosilane ((CH3)2SiCl2) solution is added to the magnesium chloride solution to form a precursor solution.
[0071] (2) Under continuous stirring conditions, the prepared precursor solution is added dropwise to the precipitant at a rate of 5 / mL, while controlling the pH value of the solution to be approximately 9-10. After the addition is completed, stirring is continued for 2 hours, and then the solution is allowed to stand for aging for 5 hours to obtain a hybrid material formed by the silicon compound and magnesium hydroxide. The hybrid material is washed with deionized water until the chloride ion is basically present to obtain a hybrid material gel.
[0072] (3) Measure 180 mL of anhydrous ethanol and pour it into the hybrid material gel, stir it thoroughly for 1.5 hours, and then filter it. Repeat the above steps twice to obtain the hybrid material alcohol gel. Ordinary drying and flowing nitrogen drying under normal pressure are used, and finally baking is carried out at 550°C for 2 hours to obtain organosilicon-magnesium oxide hybrid nanopowder. The particle size is adjusted by increasing the precursor concentration, extending the reaction and aging time, and increasing the aging temperature. In this embodiment, the D50 particle size is controlled to be 80 nm.
[0073] S4, after attaching release films to both sides of the substrate green body, flat plates are pressed together, the binder is removed, and sintered to obtain an alumina ceramic substrate; specifically,
[0074] like Figure 1-2 As shown, the operation of the flat plate pressing is: the primary membrane sheets are bonded to each other along the A surface (the bonding interface is coated with a wetting modifier layer 5) to form a green gasket 3; a release film 4 (silicone oil release film, Sichuan Yuxi New Materials Co., Ltd., 188um) of 150*150mm is taken and respectively bonded to the upper and lower sides of the substrate green 3; multiple green gaskets 3 can be stacked as needed, and separated by release films 4, so that multiple green gaskets 3 can be pressed at the same time to improve production efficiency; a punching machine is used to punch the cast film into 150*150mm specifications as green gaskets, and the green The gasket includes an upper green gasket 21 and a lower green gasket 22, and the green gaskets are respectively attached to the upper and lower ends of the substrate green 3 covered with the release film 4, wherein the thickness of the upper green gasket 21 is 3 times the thickness of the primary diaphragm, and the thickness of the lower green gasket 22 is 0.8 times the thickness of the primary diaphragm, and are placed in a flat-plate vulcanizer. The upper green gasket and the lower green gasket are respectively connected to the flat pressing plates 1 at the upper and lower ends, and are pressed by the flat-plate vulcanizer to obtain a substrate green with high density and flatness; the flat pressing parameter conditions are: pressure 12Mpa, holding temperature 60°C, and holding time 20s.
[0075] It should be noted that the flat plate 1 of the flat vulcanizer of the present invention uses a rigid material instead of a conventional silicone material. The cooperation between the flat plate 1 made of a rigid material and the green blank gasket is conducive to the positioning of the substrate green blank 3, so that its stress is evenly dispersed. The flat plate 1 of this embodiment uses a tungsten steel plate, and has a high flatness (flatness ≦0.01). The heating system uses electric heating wire heating. Tungsten steel has high hardness, wear resistance, good strength and toughness. Its high hardness and wear resistance remain basically unchanged even at a temperature of 500°C.
[0076] Among them, the design of the mold of the flat vulcanizer: the flat plate 1 at the upper and lower ends is respectively provided with a first boss 11 and a second boss 12, the first boss 11 is 2mm high, the cross section is arc-shaped, its width gradually increases from top to bottom, and the bottom area completely covers the base plate green body 3; the second boss 12 is 2mm high, the cross section is trapezoidal, and the bottom surface of the first boss 11 is flush with the upper surface of the second boss 12. The first boss 11 with an arc-shaped structure is conducive to dispersing pressure during the pressing process and improving the uniformity of the force in all directions; and the trapezoidal structure of the second boss 12 can improve stability.
[0077] The debinding and sintering are carried out by using an AB furnace, specifically:
[0078] Debinding the substrate green body in furnace A at a temperature of 350° C. and a heating rate of 0.1° C. / min;
[0079] The substrate green body is sintered in furnace B, and the sintering program is set as follows:
[0080] Heating stage: 360~850℃, heating rate: 1.5℃ / min;
[0081] The heating stage is 850~1540℃, and the heating rate is 2℃ / min.
[0082] In the insulation stage, keep the temperature at 1540℃ for 2.5h;
[0083] The temperature drop period is 1540~1000℃, and the temperature drop rate is 1.5℃ / min;
[0084] The temperature drop period is 1000-700℃, and the temperature drop rate is 0.5℃ / min;
[0085] Cooling stage: 700~25℃, natural cooling.
[0086] Example 2
[0087] A method for preparing an alumina ceramic substrate is different from Example 1 in that: this embodiment does not add a green sheet gasket; specifically:
[0088] Steps S1-S3 are the same as those in Example 1;
[0089] S4, after attaching release films to both sides of the substrate green body, flat-plate pressing, debinding, and sintering to obtain an alumina ceramic substrate;
[0090] The flat plate pressing is specifically as follows: a silicone oil release film of 150*150mm is respectively attached to the upper and lower sides of the substrate green body, and placed in a flat plate vulcanizer, the silicone oil release film is connected to the pressing plate, and pressed by the flat plate vulcanizer to obtain a substrate green body with high density and flatness; the heating system of the flat plate vulcanizer adopts electric heating wire heating, the pressing plate is a tungsten steel pressing plate (flatness ≤0.01), the pressure is 12Mpa, the holding temperature is 60°C, and the holding time is 20s.
[0091] Example 3
[0092] A method for preparing an alumina ceramic substrate is different from Example 1 in that the thickness of the upper green gasket is twice the thickness of the primary diaphragm, and the thickness of the lower green gasket is 1 times the thickness of the primary diaphragm.
[0093] Example 4
[0094] A method for preparing an alumina ceramic substrate, which is different from Example 1 in that:
[0095] The wettability modifier is a mixture of the following components in parts by mass: 100 parts of organosilicon-magnesium oxide hybrid nanopowder, 3 parts of sodium carboxymethyl cellulose, 8 parts of water, and 80 parts of n-propanol. The viscosity of the wettability modifier at 25° C. is 122 cp.
[0096] Example 5
[0097] A method for preparing an alumina ceramic substrate, which is different from Example 1 in that:
[0098] The wettability modifier is a mixture of the following components in parts by mass: 100 parts of organosilicon-magnesium oxide hybrid nanopowder, 8 parts of sodium carboxymethyl cellulose, 12 parts of water, and 80 parts of isopropanol. The viscosity of the wettability modifier at 25° C. is 150 cp.
[0099] Example 6
[0100] A method for preparing an alumina ceramic substrate is different from Example 1 in that the D50 particle size of the organosilicon-magnesium oxide hybrid nanopowder used in this example is 100 nm.
[0101] Example 7
[0102] A method for preparing an alumina ceramic substrate is different from Example 1 in that the D50 particle size of the organosilicon-magnesium oxide hybrid nanopowder used in this example is 120 nm.
[0103] Example 8
[0104] A method for preparing an alumina ceramic substrate is different from Example 1 in that no boss is provided on the tungsten steel plate, and the entire flat pressing plate is directly connected to the green gasket.
[0105] Example 9
[0106] A method for preparing an alumina ceramic substrate is different from Example 1 in that a boss is provided on the tungsten steel plate, the contact surface of the boss connected to the green sheet gasket matches the shape of the substrate green sheet, and the boss is rectangular.
[0107] Example 10
[0108] A method for preparing an alumina ceramic substrate is different from that of Example 1: the flat plate pressing parameter conditions are: pressure 10 MPa, holding temperature 70° C., and holding time 30 s.
[0109] Embodiment 11
[0110] A method for preparing an alumina ceramic substrate is different from that of Example 1: the flat plate pressing parameter conditions are: pressure 15 MPa, holding temperature 50° C., and holding time 10 s.
[0111] Comparative Example 1
[0112] A method for preparing an alumina ceramic substrate is different from Example 1 in that: this comparative example uses oily paper of the same specification instead of the silicone oil release film; the oily paper is purchased from Bochen Paper Company.
[0113] Comparative Example 2
[0114] A method for preparing an alumina ceramic substrate is different from Example 1 in that: in this comparative example, no wettability modifier is applied on the A surface of the primary diaphragm.
[0115] Comparative Example 3
[0116] A method for preparing an alumina ceramic substrate, which is different from Example 1 in that the steps are as follows:
[0117] S1, tape casting to prepare cast film, punching and tableting;
[0118] S2, coating the cast film sheets with a wettability modifier on the B surface, and then laminating the two cast film sheets together along the B surface to form a primary film sheet;
[0119] S3, coating the surface A of the primary membrane with a wettability modifier, and then bonding the primary membranes to each other through the treated surface A to form a substrate green body;
[0120] S4, after pasting release films on both sides of the substrate green body, pressing the plates together, removing binder, and sintering to obtain an alumina ceramic substrate.
[0121] Comparative Example 4
[0122] A method for preparing an alumina ceramic substrate is different from Example 1: this comparative example adopts a warm isostatic pressing process instead of flat plate pressing; the warm isostatic pressing process comprises the following steps: placing the laminated film in a PE bag and vacuuming it for packaging, placing it in an isostatic press cavity and pressing it under pressure, and the parameter conditions are: the isostatic pressing temperature is 80°C, the pressure is 150MPa, and the isostatic pressing time is 120s.
[0123] Performance Testing
[0124] 1. Morphology characterization
[0125] The alumina ceramic substrates of Example 1 and Comparative Example 4 were observed on the surface;
[0126] like Figure 3 As shown, the surface of the alumina ceramic substrate of Example 1 is smooth without bulges or bubbles;
[0127] like Figure 4 As shown, the alumina ceramic substrate subjected to static pressure treatment in Comparative Example 4 has small bulges and bubbles on its surface.
[0128] The substrate green body of the present invention has no surface bulging or bubbles, and the surface of the ceramic substrate prepared after the substrate green body is debinded and sintered is smooth and flat, and there are no other appearance defects. Comparative Example 4 has bulging and bubbles, mainly because vacuuming cannot completely avoid the residual gas in the PE bag, and the surface of the PE bag is deformed and wrinkled during vacuuming, causing bubbles and bulging on the surface of the green sheet in the PE bag due to heat.
[0129] 2. Performance Testing
[0130] The alumina ceramic substrates of Examples 1-11 and Comparative Examples 1-4 were tested for bending strength, density and warpage. The results are shown in Table 1.
[0131] (1) The flexural strength test method is: a three-point bending test is performed using a universal testing machine;
[0132] (2) Density is measured by the Archimedean displacement method, which uses the weight difference between the ceramic sample in air and water to calculate;
[0133] (3) The warpage test method is: plug gauge measurement method;
[0134] The experimental steps include: starting from one corner of the substrate, inserting the feeler gauge to measure the height of the corner, then measuring the height of other corners of the substrate in turn, and recording the height value of each corner.
[0135] Calculate the warpage:
[0136] Select the highest and lowest points measured and calculate the height difference between them.
[0137] The formula for calculating the warpage is: Warpage = (height of the highest point of the substrate diagonal length - height of the lowest point) × 100%.
[0138] Table 1
[0139]
[0140] The results show that the bending strength of the alumina ceramic substrate of the present invention is above 487Mpa and the density is 3.718g / cm 3 The above meets the requirements of the standard GB / T 5593-2015 electronic component structural ceramic materials; and the warpage is less than 0.3%, with good flatness.
[0141] In Comparative Example 1, when oily paper is used instead of silicone oil release film, the bending strength of the ceramic substrate decreases and the warpage is too high; the reason is that the oily paper is relatively rough, the transparent film is relatively soft, and it is easy to wrinkle; while the silicone oil surface of the silicone oil release film of the present invention has a small roughness and a suitable peeling force, is easy to separate, and the surface finish of the blank is relatively high.
[0142] In Comparative Example 2, the interlayers of the ceramic substrate were not coated with a wettability modifier, resulting in decreased adhesion, decreased flexural strength, and increased warpage.
[0143] In Comparative Example 3, a wettability modifier is coated on the rough surface. Since the density of the rough surface is low, the coated wettability modifier easily penetrates into the interior of the membrane and is not easy to completely debind, resulting in decreased flexural strength and higher warpage.
[0144] In Comparative Example 4, the warm isostatic pressing process was used but the residual gas could not be completely removed, and bubbles and bulges appeared on the surface of the green sheet in the PE bag due to the heat, the density decreased, and the warpage was too high.
[0145] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing an alumina ceramic substrate, characterized in that: The following steps are involved: S1, obtaining an alumina cast film, and marking two sides of the cast film as a smooth surface and a rough surface respectively according to the surface roughness; S2, laminating the cast films to each other through the rough surfaces to form a primary film sheet; S3, coating the smooth surface of the primary membrane with a wettability modifier, and then bonding the primary membranes to each other through the treated smooth surfaces to form a substrate green body; S4, after pasting release films on both sides of the substrate green body, pressing the plates together, removing binder, and sintering to obtain an alumina ceramic substrate.
2. The method for preparing an alumina ceramic substrate according to claim 1, characterized in that: In step S1, the roughness of the smooth surface is ≤0.2 μm, and the roughness of the rough surface is 0.3-0.5 μm.
3. The method for preparing an alumina ceramic substrate according to claim 1, characterized in that: In step S3, the wettability modifier includes the following components in parts by weight: 100 parts of organic-inorganic hybrid nano powder, 3-8 parts of dispersant, 8-12 parts of water, and 60-80 parts of C1-C4 fatty alcohol.
4. The method for preparing an alumina ceramic substrate according to claim 3, characterized in that: In the organic-inorganic hybrid nano powder, the organic matter is selected from dimethyldichlorosilane and / or diphenyldichlorosilane, and the inorganic matter is selected from at least one of magnesium oxide, titanium dioxide, calcium oxide, silicon oxide, vanadium oxide or lanthanum oxide.
5. The method for preparing an alumina ceramic substrate according to claim 3, characterized in that: The D50 particle size of the organic-inorganic hybrid nano powder is 50-200nm.
6. The method for preparing an alumina ceramic substrate according to claim 1, characterized in that: In step S4, the release film is a silicone oil release film with a film thickness of 150-250 μm, a roughness of 0.01-0.1 μm, and a peeling force of 5-8 g.
7. The method for preparing an alumina ceramic substrate according to claim 1, characterized in that: In step S4, the conditions for pressing the flat plates are: pressing temperature 50-70°C, pressure 10-15Mpa, and holding time 10-30s.
8. The method for preparing an alumina ceramic substrate according to claim 1, characterized in that: In step S4, the flat plate pressing step is: after the release films are attached to the two sides of the substrate green body, the green body gaskets are attached to the two side surfaces, and then placed on the pressing plate of the flat plate pressing device for pressing.
9. The method for preparing an alumina ceramic substrate according to claim 1, characterized in that: In step S4, the sintering conditions are: sintering temperature 1535-1545°C, and holding time 2-3h.
10. An alumina ceramic substrate, characterized in that: The alumina ceramic substrate is made by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing aluminum nitride ceramic substrate
CN106116589A